2015
DOI: 10.7589/2013-11-293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Herpesvirus Associated with a Penile Proliferative Lesion in a Beluga (Delphinapterus leucas)

Abstract: The carcass of an adult male beluga (Delphinapterus leucas) was found beach cast in 2008 on the shore of the St. Lawrence Estuary at Riviè re-Ouelle, Quebec, Canada. The carcass was transported to the Faculté de mé decine vé té rinaire of the Université de Montré al for postmortem examination. Aspiration pneumonia was the probable cause of death. Necropsy revealed a focal papilloma-like penile lesion, characterized by focal mucosal thickening with disorganization of the epithelial layers and lymphoplasmacytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Cases of ulcerative or proliferative dermatitis and possibly esophageal ulcers due to a herpes virus have been reported in captive and wild belugas (Martineau et al 1988, Barr et al 1989, as well as in several other species of cetaceans including bottlenose dolphins (Manire et al 2006) and dusky dolphins Lagenorhynchus obscurus (Van Bres sem et al 1994). Recently, a penile lesion positive for a herpesvirus by PCR was described in an SLE beluga (Bellehumeur et al 2015), disseminated fatal herpesvirus infection was described in an immature female bottlenose dolphin (Blanchard et al 2001), and fatal herpesviral encephalitis was described in a harbor porpoise Phocoena phocoena (Kennedy et al 1992). Our report is the first case of fatal disseminated herpesvirus in a beluga, but the significance of this virus for the CI beluga stock is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of ulcerative or proliferative dermatitis and possibly esophageal ulcers due to a herpes virus have been reported in captive and wild belugas (Martineau et al 1988, Barr et al 1989, as well as in several other species of cetaceans including bottlenose dolphins (Manire et al 2006) and dusky dolphins Lagenorhynchus obscurus (Van Bres sem et al 1994). Recently, a penile lesion positive for a herpesvirus by PCR was described in an SLE beluga (Bellehumeur et al 2015), disseminated fatal herpesvirus infection was described in an immature female bottlenose dolphin (Blanchard et al 2001), and fatal herpesviral encephalitis was described in a harbor porpoise Phocoena phocoena (Kennedy et al 1992). Our report is the first case of fatal disseminated herpesvirus in a beluga, but the significance of this virus for the CI beluga stock is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the association of herpesviruses and papillomaviruses with genital lesions in other marine mammal species, we added the penis masses to the molecular study. Papillomavirus assays were performed using a seminested PCR that amplifies a segment of the E1 gene of papillomaviruses (Rector et al 2005) and a conventional PCR allowing the amplification of the papillomavirus expected 402-bp L1 DNA fragment of common and Indo-Pacific bottlenose dolphins (Tursiops aduncus) and from a bowhead whale (Balaena mysticetus) (Bellehumeur et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Skin lesions have been attributed to a herpesvirus etiology in cetacean species by three diagnostic criteria: 1) their gross or histologic appearance (Greenwood et al 1974;Baker 1992;Baker and Martin 1992), 2) ultrastructural demonstration of herpeslike viral particles (Martineau et al 1988;Barr et al 1989;Van Bressem et al 1994), and 3) molecular criteria (Smolarek Benson et al 2006;Sierra et al 2014). Genital herpesvirus lesions have been described associated with plaquelike or proliferative wounds in bottlenose and Risso's dolphins (Tursiops truncatus and Grampus griseus; Smolarek Benson et al 2006), two Blainville's beaked whales (Mesoplodon densirostris; Saliki et al 2006;Smolarek Benson et al 2006), and a beluga whale (Delphinapterus leucas; Bellehumeur et al 2015). Except for the harbor porpoise (Phocoena phocoena), molecular diagnosis was performed on all those cases, and the corresponding sequences are available in GenBank.…”
Section: Introductionmentioning
confidence: 99%
“…A pan-herpesvirus nested PCR assay performed on a frozen tissue lesion from the beluga from the St. Lawrence River was positive, and sequencing of the amplified DNA fragment revealed the identity to be an alphaherpesvirus tentatively named beluga whale herpes virus (BWHV). Virus isolation attempts utilizing a primary beluga whale kidney (BWK) cell line were negative, probably due to the advanced state of decomposition of the carcass (Bellehumeur et al 2015). Subsequent evaluation of archived material from other dead stranded beluga suggested that BWHV is endemic in the St. Lawrence Estuary beluga population (Bellehumeur et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Virus isolation and propagation in cell cultures of herpesviruses from cetaceans have not been reported, probably due to the lack of available permissive cell lines. Other pathologies associated with herpesvirus infection in cetaceans include proliferative dermatitis in an Atlantic bottlenose dolphin (Tursiops truncatus) , penile lesions in a dead stranded beluga, from the St. Lawrence River Estuary (Bellehumeur et al 2015), encephalitis in a harbour porpoise (Phocoena phocoena) (Kennedy et al 1992), interstitial nephritis in a beaked whale (Mesoplodon densirostris) (Arbelo et al 2012), and lymphoid necrosis, also in a beaked whale (Arbelo et al 2010). A pan-herpesvirus nested PCR assay performed on a frozen tissue lesion from the beluga from the St. Lawrence River was positive, and sequencing of the amplified DNA fragment revealed the identity to be an alphaherpesvirus tentatively named beluga whale herpes virus (BWHV).…”
Section: Introductionmentioning
confidence: 99%